2017
DOI: 10.1002/smll.201604115
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Anatase TiO2 Nanosheets for High‐Performance Photocatalytic Hydrogen Production

Abstract: An ethanol solvothermal route has been developed to prepare ultrathin anatase TiO nanosheets with dominant {001} facets (≈97%), a thickness of ≈2.5 nm, and a side length of ≈200 nm. The introduction of ethanol solvent significantly enhances the content of surface chemisorbed F on the TiO nanosheet, which has a higher stability and further lowers the surface energy of {001} facets, giving rise to the large percentage of active {001} facets. Adopting well-defined morphology, such nanosheets loaded with 1 wt% Pt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…Cu-loaded anatase particles are a good photocatalyst for CO 2 photoreduction with formation of CO [49]. A theoretical model was suggested for the photocatalytic cycle on Cu-loaded (101) surface of anatase, in which CO 2 adsorption at the Cu 4 -TiO 2 interface is strong (∆H ads = −126 kJ/mol) with formation of carbonate.…”
Section: Metal-loaded Tio 2 Surfacesmentioning
confidence: 99%
“…Cu-loaded anatase particles are a good photocatalyst for CO 2 photoreduction with formation of CO [49]. A theoretical model was suggested for the photocatalytic cycle on Cu-loaded (101) surface of anatase, in which CO 2 adsorption at the Cu 4 -TiO 2 interface is strong (∆H ads = −126 kJ/mol) with formation of carbonate.…”
Section: Metal-loaded Tio 2 Surfacesmentioning
confidence: 99%
“…In another study, the synthesis of TiO 2 solid and hollow nanocubes have been demonstrated, as shown in Figure 2, and applied for the photocatalytic-mediated synthesis of benzimidazole under UV and visible conditions [46]. Similarly, TiO 2 with different morphologies such as nanospheres, nanocubes, nanotubes, nanorods, nanoflowers, nanosheets, and nanofibers have been synthesized and studied for their photocatalytic applications [47][48][49][50][51][52][53]. The size and morphology control over TiO 2 photocatalyst exhibit significant influences over their (i) optical properties such as tunable band-gap energy, repositioning of band edge positions, visible light absorption, etc., (ii) electronic properties such as increased carrier lifetime, enhanced photocurrent conduction, reduced recombination, and (iii) surface properties such as enhanced surface energy, porous structures, enhanced surface adsorption, etc.…”
Section: Morphology-dependent Photocatalytic Properties Of Tiomentioning
confidence: 99%
“…Due to their unusual physical, electrical and chemical properties and attractive applications in the field of the electrochemistry and electronics, nanosheets are being widely studied [1,2]. Nanosheets are nanostructured materials that have a shape of sheet whose thickness is lesser than 100 nm and their length is by the order of a few micrometers [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their unusual physical, electrical and chemical properties and attractive applications in the field of the electrochemistry and electronics, nanosheets are being widely studied [1,2]. Nanosheets are nanostructured materials that have a shape of sheet whose thickness is lesser than 100 nm and their length is by the order of a few micrometers [2,3]. Commonly, nanosheets are synthesized either by exfoliation or hydrothermal and solvothermal processes [1][2][3][4][5][6][7] and they have been applied to Li-ion batteries and supercapacitors for improving the charge and discharge time, and in solar cells [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation